Attitudes toward successful aging in individuals with chronic disease aged 65 or over - Aykut Aydın; Aylin Aydın Sayılan (National Scientific Medical Center, 2021)
Aim: To determine the relationship between attitudes toward aging and old age, and successful aging in individuals with chronic disease aged 65 or over.  Methods: The Attitude Scale toward Aging and Elderliness and the Successful Aging Scale were employed in this descriptive, cross-sectional, comparative study. Data were expressed as frequency, percentage, mean, and standard deviation and were analyzed using the Kolmogorov-Smirnov test, the t test, One-Way ANOVA, and Pearson correlation analysis. p values <0.05 were regarded as significant. Results: Individuals with chronic disease had greater difficulty in accepting old age, greater social exhaustion, greater abilities to cope with problems, and higher successful aging scores. Conclusion: This study shows that despite their negative attitudes toward old age, individuals with chronic disease had greater abilities to cope with problems and aged more successfully.